Lipoproteins as substitutes for serum in Mycoplasma culture medium. - Washburn, L R (J Clin Microbiol, 1979)
Crude lipoprotein-containing fractions obtained from sera of three different animal species were tested, in combination with bovine serum in Mycoplasma pneumoniae culture medium. All sera yielded at least one lipoprotein-containing component which was considerably more effective in promoting mycoplasma growth than the unfractionated serum sample from which it was derived. The very low activity of certain whole-serum samples tested in this investigation suggests that toxic substances may be present in whole serum which are not contained in the lipoprotein preparations. The greatest activity appeared in the high-density lipoprotein-containing components of bovine and horse sera and the low-density lipoprotein-containing components of human serum. The high degree of growth-supporting activity of these crude lipoprotein-containing serum components suggests that they may be useful as serum substitutes in mycoplasma culture media.